Bisphenol-A exposure during pregnancy alters pancreatic β-cell division and mass in male mice offspring: A role for ERβ. (November 2020) - Boronat-Belda, Talía; Ferrero, Hilda; Al-Abdulla, Ruba; Quesada, Iván; Gustafsson, Jan-Ake; Nadal, Ángel; Alonso-Magdalena, Paloma
Abstract: Bisphenol-A (BPA) is a widespread endocrine disrupting chemical that constitutes a risk factor for type 2 diabetes mellitus (T2DM). Data from animal and human studies have demonstrated that early exposure to BPA results in adverse metabolic outcomes in adult life. In the present work, we exposed pregnant heterozygous estrogen receptor β (ERβ) knock out (BERKO) mice to 10 μg/kg/day BPA, during days 9–16 of pregnancy, and measured β-cell mass and proliferation in wildtype (WT) and BERKO male offspring at postnatal day 30. We observed increased pancreatic β-cell proliferation and mass in WT, yet no effect was produced in BERKO mice. Dispersed islet cells in primary culture treated with 1 nM BPA showed an enhanced pancreatic β-cell replication rate, which was blunted in pancreatic β-cells from BERKO mice and mimicked by the selective ERβ agonist WAY200070. This increased β-cell proliferation was found in male adult as well as in neonate pancreatic β-cells, suggesting that BPA directly impacts β-cell division at earliest stages of life. These findings strongly indicate that BPA during pregnancy upregulates pancreatic β-cell division and mass in an ERβ-dependent manner. Thus, other natural or artificial chemicals may use this ERβ-mediated pathway to promote similar effects.